The implementation of strategic management process by small/ medium scale industry (SMI) / Siti Nooremy Sariman .. [et al.] - Sariman, Siti Nooremy (2001)
The crucial role of Small and Medium Industries (SMIs) in Malaysia's industrialisation process has been clearly stated in the Second Outline Perspective Plan (OPP2) (1991-2000) and the Sixth Malaysia Plan (6MP) (1990-1995). SMIs are promoted and upgraded in line with the national industrial policy to create inter and intra industry linkages and ensure the success of the larger industries. Thus, for the period 1994, MITI's efforts have been directed towards the qualitative rather than the quantitative development of SMIs. This is imperative for the development of a strong, viable and competitive support industry that is capable of meeting the requirements of larger industries. In addition to this, qualitative development also aims to develop more SMIs which are export oriented. Penetration into the export market demands improvements in product quality, production capacity, pricing and marketing strategies. MITI's SMI development programmes have been developed to achieve this aim. In addition to existing incentives under the Promotion of Investment Act 1986, several programmes for SMI development have been implemented. The programmes implemented to date cover the areas of finance, market, technology, training, infrastructure and information support. For the year 1995, existing programmes will be expanded and enhanced to enable more SMIs to be upgraded in line with Malaysia's vision of achieving a fully industrialised nation status by the year 2020.